2007
DOI: 10.1152/ajpregu.00067.2007
|View full text |Cite
|
Sign up to set email alerts
|

Preoptic norepinephrine mediates the febrile response of guinea pigs to lipopolysaccharide

Abstract: Norepinephrine (NE) microdialyzed in the preoptic area (POA) raises core temperature (Tc) via 1) α1-adrenoceptors (AR), quickly and independently of POA PGE2, and 2) α2-AR, after a delay and PGE2 dependently. Since systemic lipopolysaccharide (LPS) activates the central noradrenergic system, we investigated whether preoptic NE mediates LPS fever. We injected LPS (2 μg/kg iv) in guinea pigs prepared with intra-POA microdialysis probes and determined POA cerebrospinal (CSF) NE levels. We similarly microdialyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 68 publications
4
42
0
1
Order By: Relevance
“…The novel finding that Cirazoline induced a rapid-onset hyperthermia independent of PGE 2 production suggested that alpha-1 ARs have an important role in the early development of a febrile response (Feleder et al, 2007). Antagonism of the alpha-1 ARs adds support for this observation, ultimately hindering rapid onset of fever and reducing its high point (Feleder, 2004).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The novel finding that Cirazoline induced a rapid-onset hyperthermia independent of PGE 2 production suggested that alpha-1 ARs have an important role in the early development of a febrile response (Feleder et al, 2007). Antagonism of the alpha-1 ARs adds support for this observation, ultimately hindering rapid onset of fever and reducing its high point (Feleder, 2004).…”
Section: Discussionmentioning
confidence: 97%
“…This early hyperthermia likely attenuates due to eventual desensitization at the postsynaptic alpha-1 ARs, the induction of COX-2 expression by activation of alpha-2 ARs, ensuing PGE 2 synthesis, and action at Prostaglandin E receptors (EP; presumably the EP 3 subtype) which contribute the late phase of fever (Feleder et al, 2007;Lazarus et al, 2007;Oka, 2004). The application of norepinephrine in the POAH has been shown to increase the frequency of spontaneous, miniature inhibitory postsynaptic currents (IPSCs) via the alpha-1 AR, and likewise decrease the frequency of IPSCs via the alpha-2 AR (Kolaj and Renaud, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, how norepinephrine acts on the febrile local mechanism in the POA is unknown. Although adrenoreceptor agonists and antagonists have been applied into the POA to examine their effects on LPS-or PGE 2 -induced fever, inconsistent results have been obtained (37,128). Noradrenergic inputs to the POA are likely provided by A1, A2, and locus coeruleus neurons in the pons and the medulla oblongata (184).…”
Section: Central Processing Of Pyrogenic Signals For Fever Developmentmentioning
confidence: 99%
“…These findings therefore indicated that NO could, in turn, modulate monoaminergic neurotransmission in the central nervous system. Evidence for the putative involvement of NE and ␣ 1 -AR in the initiation of fever was presented in our companion paper (15). Hence the existence of a mutually antagonistic NE-NO interaction in the POA in response to intravenous LPS is plausible.…”
mentioning
confidence: 90%